Pengembangan Media Pembelajaran Berbasis Canva “SAHABAT” untuk Meningkatkan Pemahaman Akhlak terhadap Allah, Orang Tua, dan Guru - Irpan Jamil; Kelvin Krisnadi Adi Nugraha; Ani Nur Aeni; Rizqiyah Rizqiyah (Lembaga Yasin AlSys, 2026)
Elementary school students’ low understanding of moral conduct toward Allah, parents, and teachers is an important issue in character learning because the learning process is still dominated by lecture methods, the use of less varied media, and the suboptimal use of digital technology. This study aims to develop and analyze the feasibility and effectiveness of Canva-based “SAHABAT” learning media in improving students’ understanding of moral conduct toward Allah, parents, and teachers. This study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of needs analysis, product design, media development, classroom implementation, and evaluation. The research subjects were elementary school students. Data were collected through material expert and media expert validation sheets, student response questionnaires, and pre-test and post-test assessments to measure the improvement of students’ understanding. The results show that the Canva-based “SAHABAT” learning media obtained a highly feasible category based on expert validation. Students’ responses to the use of the media were in the very good category, as indicated by increased interest, attention, and involvement in learning. The results of the pre-test and post-test analysis also showed an improvement in students’ understanding of moral conduct material. The conclusion of this study emphasizes that the Canva-based “SAHABAT” learning media is feasible, useful, and effective in improving students’ understanding of moral conduct toward Allah, parents, and teachers. The implications of this study indicate that the use of innovative and interactive digital learning media can serve as an alternative for teachers in supporting character learning that is more engaging, meaningful, and aligned with technological development.